Bifidobacterium from infant stool: the diversity and potential screening - DYAH FITRI KUSHARYATI; HENDRO PRAMONO; DINI RYANDINI; TSANI ABU MANSHUR; MEILANY ARIATI DEWI; KHUSNUL KHATIMAH; Anwar Rovik (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kusharyati DF, Pramono H, Ryandini D, Manshur TA, Dewi MA, Khatimah K, Rovik A. 2020. Bifidobacterium from infant stool: the diversity and potential screening. Biodiversitas 21: 2506-2513. Bifidobacteria spp. are a group of Lactic Acid Bacteria commonly found in the gastrointestinal tract of adults and infants. LAB are known as probiotics and have many health benefits. This research aimed to isolate Bifidobacteria from infant stool, identify, explore their diversity, and screen their potential as probiotics. Stool samples were collected from 3 healthy infants in Banyumas Regency. The potential screening included lysozyme resistance, antimicrobial activity, and exopolysaccharide production. A total of 7 Bifidobacterium species were isolated from infant stool: B. catenulatum, B. minimum, B. indicum, B. dentium, B. asteroides, B. galicum, and B. coerinum. B. indicum isolates (Bb3F and Bb1B) had the greatest inhibition activity against Escherichia coli and Candida albicans with 10.80 and 9.70 mm, respectively. Bifidobacteria isolates were resistant to lysozyme from egg whites up to 200 µg.mL-1. B. catenulatum Bb1A isolate had the highest yield of exopolysaccharide production with 74 mg.L-1. Among them, three Bifidobacterium strains (Bb1B, Bb2A, and Bb2E) were considered potentially as probiotics.